SILENT EXODUS DALAM GEREJA: KAJIAN TEOLOGIS TERHADAP FENOMENA JEMAAT YANG MASIH BERIBADAH TETAPI KEHILANGAN KETERIKATAN EKLESIAL - Kristia Mesaarruan; Daniel Sampe Ruru; Irvan Yoga; Yuyun; Feby Febryanti (CV. ADIBA AISHA AMIRA, 2026)
The phenomenon of silent exodus emerges when congregants continue to participate in worship—whether physically or virtually yet undergo a degradation of communal attachment and spiritual commitment. This study analyzes the phenomenon from a theological-ecclesiological perspective using a qualitative-descriptive approach based on library research,. Data analysis employs the Miles & Huberman technique, which involves data reduction, data display, and verification through content analysis,. The research findings identify several key contributing factors: individualism, consumerism, digitalization, church leadership crises, and the cultural shifts of the younger generation. From an ecclesiological standpoint, the church is ideally the